Metallophthalocyanines as optical active dopants in borate glass. (September 2021) - Popanda, Barbara; Środa, Marcin; Słota, Rudolf; Zakrzyk, Maja
Abstract: B2 O3 – phthalocyanine composites (B2 O3 @MPc) were synthesized at 410 °C by sintering boron trioxide doped with base metal-free phthalocyanine (H2 Pc) and/or its complexes of Mg, Zn, Gd (Pc = C32 H16 N8, phthalocyanine ligand, M = metal ion). The glassy products were characterized by scanning electron microscopy (SEM, EDS) and diffuse reflectance spectroscopy (DRS) which confirmed the incorporation of the respective phthalocyanines into the amorphous borate matrix. FTIR results suggested a possible impact of the phthalocyanine dopants on the final solid structure of the glassy matrix. The UV-excited composites emitted a pronounced blue phosphorescence featured by a two-step quenching process and lifetimes of 28 and 670 ms. Optical stimulated luminescence (OSL) tests proved excellent luminescence properties revealed by the samples including H2 Pc and GdPc2 dopants. Reversible photoconductivity of the composites was confirmed by impedance spectroscopy measurements at current frequencies of 10 3 and 10 2  Hz and UV irradiation. The best results exhibited B2 O3 @GdPc2 featuring an impedance modulus decrease of about 2 orders of magnitude at 10 2  Hz compared to the other composites. Highlights: B2 O3 – phthalocyanine composites show luminescence properties. Two independent luminescence lifetimes were estimated for all composites. Composite doped Gd-phthalocyanine shows excellent photoconductivity. Composite doped Mg-phthalocyanine shows linearity optically stimulated luminescence.